Chapter Global urban humanity - the "embodiment" of embodying peripheries - Hwa, Kuan (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
Human "embodiment" is a polysemous term that has rich multi-, inter-, and transdisciplinary dimensions from various histories of consciousness. As a paradigm for various methodologies, it emphasizes the lived experience and the immanence of the human condition, especially regarding sensory habitus, bodily ways of knowing, and the material-social dimension of humanity within a historically/geographically situated context; it validates all people as bearers of their own insight and knowledge, and emphasizes that experience itself serves as a phenomenological basis for understanding. Embodiment is thus not reducible to an abstract philosophical project, but rather holds possibilities for a practical and applied ethics. In the context of peripheries, embodiment can be understood as the commitment to marginalized communities and teaches us both the scientific and humanistic value of compassion.